Research of space-object detection and tracking simulation system based on HLA - Ji-hua, Zhang; Ning, Zhao; Lei, Cai; Ru-yu, Fan; Bin, Tan; Qing-Jun, Qu (2012 2nd International Conference on Computer Science and Network Technology, 2012)
An expandable open simulation system structure based on HLA technology and against the background of detection and tracking ability analysis is designed according to the development of the current simulation technology and the actual requirements for detection tracking process and ability analysis system. Multi-sample and multi-run mechanism is designed in the paper. This paper commences the research from the design of system architecture. The federation development and run flow based on FEDFP model a remainly discussed. The performance of the system is given by this simulation system. It is stable for the structure of detection and tracking Simulation system, which is reusable for the model and convenient for the user, also, it can be used as a support platform for the simulation test of electro-optic (EO) work process and detection tracking capability.